Predicting Fetal Growth with Curve Fitting and Machine Learning - Huan Zhang; Chuan-Sheng Hung; Chun-Hung Richard Lin; Hong-Ren Yu; You-Cheng Zheng; Cheng-Han Yu; Chih-Min Tsai; Ting-Hsin Huang (Bioengineering, 2025)
Monitoring fetal growth throughout pregnancy is essential for early detection of developmental abnormalities. This study developed a Taiwan-specific fetal growth reference using a web-based data collection platform and polynomial regression modeling. We analyzed ultrasound data from 980 pregnant women, encompassing 8350 prenatal scans, to model six key fetal biometric parameters: abdominal circumference, crown–rump length, estimated fetal weight, head circumference, biparietal diameter, and femur length. Quadratic regression was selected based on a balance of performance and simplicity, with R2 values exceeding 0.95 for most parameters. Confidence intervals and real-time anomaly detection were implemented through the platform. The results demonstrate the potential for efficient, population-specific fetal growth monitoring in clinical settings.